2022
DOI: 10.1371/journal.pgph.0000623
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility patterns of pathogens isolated from laboratory specimens at Livingstone Central Hospital in Zambia

Abstract: Background Multidrug resistance (MDR) is a global problem that require multifaceted effort to curb it. This study aimed to evaluate the antibiotic susceptibility patterns of routinely isolated bacteria at Livingstone Central Hospital (LCH). Methods A retrospective study was performed on all isolated organisms from patient specimens that were processed from January 2019 to December 2021. Specimens were cultured on standard media and Kirby-Bauer disc diffusion method was employed for susceptibility testing fol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, few prior research efforts have focused on the effect of specimen type on AMR. Studies by Mwansa et al showed that Staphylococcus aureus resistance to tetracycline was influenced by specimen type, being lower in urine compared to blood [ 32 ]. Likewise, Escherichia coli isolated from sputum had higher resistance to common antibiotics compared to those isolated from blood and urine, except for urine, where Escherichia coli was more resistant to fluoroquinolones than that from sputum [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few prior research efforts have focused on the effect of specimen type on AMR. Studies by Mwansa et al showed that Staphylococcus aureus resistance to tetracycline was influenced by specimen type, being lower in urine compared to blood [ 32 ]. Likewise, Escherichia coli isolated from sputum had higher resistance to common antibiotics compared to those isolated from blood and urine, except for urine, where Escherichia coli was more resistant to fluoroquinolones than that from sputum [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scarce or no published data regarding CR or CPE were found for some regions, especially for developing countries or countries where access to carbapenems is limited [180,181]. For many countries, reported data on CPE carriage were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Zambia is a country in the sub-Saharan African (SSA) region with a reportedly high burden of infectious diseases [47][48][49]. Consequently, the presence of drug-resistant pathogens in healthcare facilities has been reported in several studies [50][51][52][53][54][55][56][57][58]. The Antimicrobial Resistance Coordinating Committee (AMRCC) hosted at the Zambia National Public Health Institute (ZNPHI) has been promoting the establishment and strengthening of AMR surveillance across the country [59,60].…”
Section: Introductionmentioning
confidence: 99%